The investigation of microstructure and strength properties of lightweight mortar containing mineral admixtures exposed to sulfate attack - Tanyildizi, Harun (Elsevier Sci Ltd, 2016)
The aim of this study was to evaluate the effect of magnesium sulfate concentration on the microstructure and strength properties of lightweight mortars containing fly ash and silica fume. Lightweight mortar specimens containing 15% fly ash and 10% silica fume were prepared for this study. The specimens were exposed to different sulfate concentrations (0% MgSO4-2, 2% MgSO4-2 and 4% MgSO4-2) for one year after specimens were kept in water at 20 +/- 2 degrees C for 28 days. The microstructure analyses and compressive strength were monitored for cure periods to evaluate the performance of the test specimens exposed to different sulfate attacks. The microstructure analyses were performed using the scanning electron microscopy, the energy-dispersive X-ray, and the X-ray powder diffraction. The microstructure results showed that the deterioration mechanism of lightweight mortars exposed to magnesium sulfate has changed according to magnesium sulfate concentration percentage and mineral admixture type. Furthermore, the compressive test results showed that the performance of lightweight mortars containing silica fume were higher than lightweight mortars without mineral admixture and with fly ash. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Lightweight mortar; Electron microscopy; Energy-dispersive X-ray; X-ray diffraction; Compressive strength